2018
DOI: 10.2174/1745017901814010026
|View full text |Cite
|
Sign up to set email alerts
|

Takotsubo Syndrome is Associated with Mood Disorders and Antidepressants Use, not with Anxiety and Impairment of Quality of Life Due to the Psychiatric Disorder

Abstract: Background:The aim was to study the association between mood and anxiety disorders and the Tako-Tsubo Syndrome (TTS) and to determine the role of antidepressants and the impairment of quality of life due the comorbid psychiatric disorder.Methods:Case-control study: 19 consecutive patients (17 female) with TTS compared to 76 controls without TTS, were randomly selected from the database of a nationwide epidemiological study after matching (gender, age and residence) by controls. Psychiatric diagnoses were carri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 27 publications
1
21
1
Order By: Relevance
“…Anxiety and depression seemed to be prevalent in the history of TTS in one study (Delmas et al, 2013), while two studies evidenced a role only for anxiety (Del Pace et al, 2011;Christensen et al, 2016). Two studies (Smeijers et al, 2016;Sancassiani et al, 2018) evidenced a role for depression (and not for general anxiety) if compared with healthy controls, but not if compared with patients with chronic heart failure (Smeijers et al, 2016). One study (Compare et al, 2018) compared the prevalence of depression in TTS with emotion triggers vs. acute myocardial infarction with emotion triggers vs. TTS without emotion trigger and found a significant prevalence only in the two groups with emotion triggers.…”
Section: Psychopathology (Current By Standardized Measures)mentioning
confidence: 95%
See 1 more Smart Citation
“…Anxiety and depression seemed to be prevalent in the history of TTS in one study (Delmas et al, 2013), while two studies evidenced a role only for anxiety (Del Pace et al, 2011;Christensen et al, 2016). Two studies (Smeijers et al, 2016;Sancassiani et al, 2018) evidenced a role for depression (and not for general anxiety) if compared with healthy controls, but not if compared with patients with chronic heart failure (Smeijers et al, 2016). One study (Compare et al, 2018) compared the prevalence of depression in TTS with emotion triggers vs. acute myocardial infarction with emotion triggers vs. TTS without emotion trigger and found a significant prevalence only in the two groups with emotion triggers.…”
Section: Psychopathology (Current By Standardized Measures)mentioning
confidence: 95%
“…Eight studies analyzed the presence of past psychopathologic diagnoses by means of psychometric tests after the occurrence of TTS (Del Pace et al, 2011;Delmas et al, 2013;Compare et al, 2014Compare et al, , 2018Kastaun et al, 2014;Christensen et al, 2016;Smeijers et al, 2016;Sancassiani et al, 2018) with miscellaneous findings. Anxiety and depression seemed to be prevalent in the history of TTS in one study (Delmas et al, 2013), while two studies evidenced a role only for anxiety (Del Pace et al, 2011;Christensen et al, 2016).…”
Section: Psychopathology (Current By Standardized Measures)mentioning
confidence: 99%
“…In most instances, TCM is observed after emotional or physical stress; a recent paper also suggested an association between TCM and depression/mood disorders [3]. However, TCM can also be related to the stress of surgery, in which case, it is called perioperative TCM (pTCM) [4].…”
Section: Introductionmentioning
confidence: 99%
“…We read with interest the article by Sancassiani et al . about a study of 19 patients with a history of Takotsubo Syndrome (TTS) who underwent psychiatric studies by means of the ANTAS-SCID and the SF-12 tools [1]. The authors found an association between TSS and depressive disorders and the use of antidepressive drugs [1].…”
mentioning
confidence: 99%